Short stature related to Growth Hormone Insensitivity (GHI) in childhood - Mastromauro, Concetta; Giannini, Cosimo; Chiarelli, Francesco (Frontiers in Endocrinology, 2023)
Linear growth during childhood results from the synergic contribution of different factors. The best growth determinant system during each period of life is represented by the Growth Hormone-Insulin like Growth Factor axis (GH–IGF), even if other several factors are involved in normal growth. Within the broad spectrum of growth disorders, an increased importance has been committed to Growth Hormone Insensitivity (GHI). GHI has been reported for the first time by Laron as a syndrome characterized by short stature due to GH receptor (GHR) mutation. To date it is recognized that GHI represents a wide diagnostic category including a broad spectrum of defects. The peculiar characteristic of GHI is the low IGF-1 levels associated with normal or elevated GH levels and lack of IGF-1 response after GH administration. Recombinant IGF-1 preparations may be used in the treatment of these patients.